SURFACE PROPERTIES OF BAMBOO AND SCOTS PINE IMPREGNATED WITH BORON AND COPPER BASED WOOD PRESERVATIVES AFTER ACCELERATED WEATHERING - Baysal, Ergun; Dizman Tomak, Eylem; Topaloglu, Elif; Pesman, Emrah (Univ Bio-Bio, 2016)
In this study, we investigated the color, gloss and surface roughness of bamboo (Phyllostachys bambusoides) and Scots pine (Pinus sylvestris) samples impregnated with boron and copper based preservatives during accelerated weathering from 168 h to 672 h. Tanalith-E, ACQ, wolmanit-CB were used as copper-based chemicals, while a mixture of boric acid and borax (7:3; w/w) was used as the boron compound. Results showed that retention values of bamboo samples were lower than the retention values of Scots pine samples probably due to the bamboo's anatomical structure and penetration characteristic. Bamboo surfaces became rougher and darker after impregnation and accelerated weathering compared to initial surfaces. Longer accelerated weathering periods seemed to have not a considerable effect on surface roughness of bamboo samples impregnated with copper based preservatives. Gloss of impregnated Scots pine samples increased with longer accelerated weathering period while gloss of bamboo samples decreased slightly with longer accelerated weathering period. Wolmanit-CB seemed to be most effective wood preservative for hindering color change and ensuring smooth surfaces after accelerated weathering. Color changes caused by accelerated weathering tended to be greater for impregnated bamboo samples than impregnated Scots pine samples.
Keywords: Accelerated weathering; bamboo; boron compounds; color; copper based preservatives; gloss; surface roughness